Attenuation of the in vivo toxicity of biomaterials by polydopamine surface modification. (July 2011) - Hong, Seonki; Kim, Keum Yeon; Wook, Hwang Jin; Park, Sung Young; Lee, Kang Dae; Lee, Dong Yun; Lee, Haeshin
Aims: Polydopamine coating is emerging as a useful method of surface functionalization due to the ability of this compound to form a nanometer-scale organic thin film on virtually any material surface to which proteins, peptides, oligonucleotides, metal ions or synthetic polymers are able to be attached. The unique properties of polydopamine make this technique suitable for nanomedicine. To facilitate the use of polydopamine, evaluation of toxicity is of great importance. In this article, we investigated the in vivo toxicity of polydopamine.Results: We found that the polydopamine functions as a biocompatible layer, attenuating adverse biological responses caused by intrinsic properties of the coated material. One-step polydopamine coating greatly reduced the inflammatory response to poly-L -lactic acid surfaces and the immunological responses of blood on quantum dots were also reduced.Conclusion: Our results indicate that polydopamine provides a versatile platform that can reduce the in vivo toxicity of biomaterials that contact tissue or blood.